A expansão urbana de Uberlândia e a ação da imobiliária Tubal Vilela - Martins, Ieda Carla; Ramires, Julio Cesar de Lima; Soares , Beatriz Ribeiro (Sociedade & Natureza, 2021)
A expansão urbana de Uberlândia e a ação da imobiliária Tubal Vilela